Transcriptomic analysis reveals distinct molecular signatures and regulatory networks of osteoarthritic chondrocytes versus mesenchymal stem cells during chondrogenesis - Lin, Tsung-Yu; Mishra, Viraj Krishna; Dubey, Rajni; Chaturvedi, Thakur Prasad; Narayan, Shankar A; Fang, Hsu-Wei; Tsai, Lung-Wen; Kumar Dubey, Navneet (Biomedical papers, 2025)
Background. Recent regenerative studies imply conflicting results on knee osteoarthritic (OA) chondrocytes and mesenchymal stem cells (MSC)-mediated cartilage constructs in terms of compressive properties and tensile strength. This could be attributed to different gene expression patterns between MSC and OA chondrocytes during chondrogenic differentiation. Therefore, we analyzed differentially expressed genes (DEGs) between OA and MSC-derived chondrocytes using bioinformatics tools.Methods. We downloaded and analyzed the GSE19664 dataset from the Gene Expression Omnibus to identify DEGs. DAVID was used to perform Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses, while a protein-protein interaction network of DEGs was constructed through the Search Tool for the Retrieval of Interacting Genes (STRING) and identified hub genes by CytoHubba.Results. A total of 43 DEGs identified (15 downregulated and 28 upregulated) were found to be deregulated between OA and MSC-derived chondrocytes. KEGG analysis revealed the enrichment of complement and coagulation cascades and other pathways among the studied chondrocytes. The pathway enrichment identified top KEGG, gene ontology biological process, molecular function, and cellular component. The hub networks identified the top 5 hub genes involved in chondrogenesis, including CLU, PLAT, CP, TIMP3, and SERPINA1.Conclusions. Our results identified significant genes involved in chondrogenesis. These findings provide new avenues for exploring the genetic mechanism underlying cartilage synthesis and novel targets for preclinical intervention and clinical treatment.
Keywords: osteoarthritis; chondrocytes; mesenchymal stem cells; differentially expressed genes (DEGs); protein-protein interaction (PPI); hub genes; gene ontology (GO)